The effect of horse saliva on the growth rate of axonopous compressus / Nik Nur Farhanis Nik Salleh - Nik Salleh, Nik Nur Farhanis (Faculty of Applied Sciences, 2017)
The grass was always greener with the presence of ruminants or grazers. This might be due to the fact that the ruminant's or grazer's secretions (eg: saliva) contributes to the growth enhancement of plants. Nevertheless, the positive effect of the saliva towards plants have yet to be explored. The aims of this study was to determine the effect of horse's saliva on the growth rate of Axonopous compressus and also the effect of trimming towards it. Axonopous compressus is a type of a grass that commonly grows in Malaysia. The results of this study showed that there is a positive response of Axonopous compressus towards the horse's saliva by sudden blooming of its growth for a group of treatment where the grass were trimmed for about 2mm before the next application of saliva was made. The length of these grasses's blade seems to have a cumulatively highest reading of length which is 16.9cm as compared to the rest of the treatment group. The second group treatment that was tested, showed a longer length of blade when the Axonopous compressus was applied with a saliva but without trimming of its blade. The reading showed an accumulative increment of blade's reading which is 6.9cm. The least increment was cumulatively 4.2cm only, which is the group that was set-up as a control. This group treatment was left without application of saliva on the Axonopous compressus and also did not undergoes trimming. The control group also showed the least weight reading after a dry weight has been obtained. While the group that was applied with saliva showed a higher weight. Thus, this experiment proved that a horse's saliva as well as trimming effected the growth rate of Axonopous compressus.